Survival after endoscopic valve therapy in patients with severe emphysema - Gompelmann, Daniela; Benjamin, Nicola; Kontogianni, Konstantina; Schuhmann, Maren; Hoffmann, Hans; Heußel, Claus Peter; Herth, Felix; Eberhardt, Ralf (Respiration, 2019)
Background: Endoscopic valve therapy leads to an improvement of lung function, exercise tolerance, and quality of life in a selected cohort of patients with advanced emphysema. So far, only few data exist on the long-term outcome. Objectives: This analysis evaluated the impact of valve therapy on the survival of emphysema patients. Methods: Survival rates of emphysema patients who underwent valve therapy were assessed according to their radiological outcome following valve placement. Results: From 2005 to 2013, 449 emphysema patients (mean age 64 ± 7 years) underwent valve therapy and were followed for a mean time of 37.3 ± 21.3 months. A total of 128 patients (29%) developed complete lobar atelectasis, 34 out of these also experienced a pneumothorax; 50 patients (11%) developed pneumothorax without lobar atelectasis, and 261 patients (58%) target lobe volume reduction or no volume change. Patients with atelectasis showed significantly better baseline forced expiratory volume in 1 second (%), residual volume (L), total lung capacity (L), and transfer factor for carbon monoxide (%; all p < 0.05), but there was no significant difference in the BODE score (p = 0.195). Patients with valve-induced lobar atelectasis had a significant survival benefit compared to patients without atelectasis (p = 0.009; 5-year survival rate 65.3 vs. 43.9%). The advent of pneumothorax in 84 patients did not influence survival (p = 0.52). Conclusions: Lobar atelectasis following endoscopic valve therapy is associated with a survival benefit.